Mind the Gap: 20 Years of Progress and Retrenchment in School Funding and Achievement Gaps. Issue 1 (11th May 2016) - Baker, Bruce D.; Farrie, Danielle; Sciarra, David G.
Abstract: Although there has been significant progress in the long term, achievement gaps among the nation's students persist. Many factors have contributed to the disparities in outcomes, and societal changes can explain progress, or lack thereof, over the past few decades. This is well documented in the 2010 Educational Testing Service (ETS) report Black–White Achievement Gaps: When Progress Stopped, which explored achievement gap trends and identified the changing conditions that may have influenced those trends. In this report, we extend that work by focusing on the relationship between school funding, resource allocation, and achievement among students from low‐income families. We tackle the assumption that greater resources, delivered through fair and equitable school funding systems, could help raise academic outcomes and reduce the achievement gap. The goal is to provide convincing evidence that state finance policies have consequences in terms of the level and distribution of resources, here limited to staffing characteristics, and that the resulting allocation of resources is also associated with changes in both the level of academic achievement and achievement gaps between low‐income children and their peers. Using more than 20 years of revenue and expenditure data for schools, we empirically test the idea that increasing investments in schools generally is associated with greater access to resources as measured by staffing ratios, class sizes, and the competitiveness of teacher wages. When the findings presented here are considered with the strong body of academic literature on the positive relationship between substantive and sustained state school finance reforms and improved student outcomes, a strong case can be made that state and federal policy focused on improving state finance systems to ensure equitable funding and improving access to resources for children from low‐income families is a key strategy to improve outcomes and close achievement gaps. Abstract : Report Number: ETS RR‐16–15